If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t + 12 = 0 Reorder the terms: 12 + 2t = 0 Solving 12 + 2t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 2t = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 2t = 0 + -12 2t = 0 + -12 Combine like terms: 0 + -12 = -12 2t = -12 Divide each side by '2'. t = -6 Simplifying t = -6
| 2/3*64-10 | | 1/8x-3/85/2x-17 | | -49=17t-10t | | (y-2)=-4x+4 | | -5=8(x-4)-5x | | (-3a)(2a)(-4a)= | | x+8=x^2+4x-7 | | 8v+2(v+2)=-36 | | -5+13=5b-8-4b | | c=.5mv | | c=1/2mv | | -4=6x+2(-4x) | | 2.5x+6y=480 | | 5n^2-2n+28=0 | | -b=4a+3c-p | | X^5-3x+2x=0 | | 2xy-5=9 | | y=5+-10x | | -10x=-12 | | 13x+29y=-23 | | 20m-7-2m=8m-2 | | 2.3m+1=1.3m+7 | | -2-2=4-2X+3X | | 1/2*x-5=10 | | Y=-3/8x-2 | | 7.34=2(3.14)r | | e^8x+3=19 | | 15*500= | | 43x+2=38 | | 4w+2-3w=7 | | -4(x-4)=-3(x-7)-4 | | 5+10-5*2+45+2x=400 |